Anti-cancer stem cell activity of a sesquiterpene lactone isolated from Ambrosia arborescens and of a synthetic derivative. - Wendy Soria Sotillo; Rodrigo Villagomez; Sandra Smiljanic; Xiaoli Huang; Atena Malakpour; Sebastian Kempengren; Gloria Rodrigo; Giovanna Almanza; Olov Sterner; Stina Oredsson (PLoS ONE)
New regimens are constantly being pursued in cancer treatment, especially in the context of treatment-resistant cancer stem cells (CSCs) that are assumed to be involved in cancer recurrence. Here, we investigated the anti-cancer activity of sesquiterpene lactones (SLs) isolated from Ambrosia arborescens and of synthetic derivatives in breast cancer cell lines, with a specific focus on activity against CSCs. The breast cancer cell lines MCF-7, JIMT-1, and HCC1937 and the normal-like breast epithelial cell line MCF-10A were treated with the SLs damsin and coronopilin, isolated from A. arborescens, and with ambrosin and dindol-01, synthesized using damsin. Inhibitory concentration 50 (IC50) values were obtained from dose-response curves. Based on IC50 values, doses in the μM range were used for investigating effects on cell proliferation, cell cycle phase distribution, cell death, micronuclei formation, and cell migration. Western blot analysis was used to investigate proteins involved in cell cycle regulation as well as in the NF-κB pathway since SLs have been shown to inhibit this transcription factor. Specific CSC effects were investigated using three CSC assays. All compounds inhibited cell proliferation; however, damsin and ambrosin were toxic at single-digit micromolar ranges, while higher concentrations were required for coronopilin and dindol-01. Of the four cell lines, the compounds had the least effect on the normal-like MCF-10A cells. The inhibition of cell proliferation can partly be explained by downregulation of cyclin-dependent kinase 2. All compounds inhibited tumour necrosis factor-α-induced translocation of NF-κB from the cytoplasm to the nucleus. Damsin and ambrosin treatment increased the number of micronuclei; moreover, another sign of DNA damage was the increased level of p53. Treatment with damsin and ambrosin decreased the CSC subpopulation and inhibited cell migration. Our results suggest that these compounds should be further investigated to find efficient CSC-inhibiting compounds.